The Impact of Social Media on Tourists' Visits at Giong Siu Tourism Destination in Mataram City - Khairunnisa, Arsila; Atmayanti, Tati (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2024)
Purpose: The rapid development of technology has had a significant impact on the economic cycle of society. This research aims to determine the impact of the use of social media on increasing the number of tourist visits to the Giong Siu tourist attraction. Method: This research uses descriptive qualitative methods with data collection techniques through observation and interviews. The technique for determining informants uses purposive sampling technique. Meanwhile, in analyzing the data, researchers used the Miles and Huberman analysis model. Then test the validity of the data in terms of credibility in the form of source triangulation. Results: The results of this research show that social media (Instagram and Facebook) have a positive impact on increasing the number of tourist visits to the Giong Siu tourist attraction. Promotion via social media is an alternative marketing strategy for introducing tourist attractions. Contribution: This research can be used as a reference in increasing efforts to develop tourist attractions in the region.